Promoting adequate and healthy food in early childhood education: a systematic review - Jéssica de Melo Araújo Moreira; Mariana Fernandez Barbosa; Rafaele Rosa Febrone; Camila da Silva de Castro; Leticia Sales Pereira; Rosane Valéria Viana Fonseca Rito (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to identify and describe the characteristics of studies that address the promotion of adequate and healthy food in early childhood education units and their repercussions on the school community. Methods: the search and selection were performed according to the PRISMA recommendations in the Medline databases via OVID, EMBASE and LILACS. Data extraction took placeusing a table developed by the authors. The evaluation of the quality of the evidence of the studies was carried out through the risk of bias using an adapted scale. Result: twelve articles that met the eligibility criteria were selected. All studies were applied in public or private educational institutions with a median of 236 participants. In the analysis of food and nutrition education activities, the most adopted with preschoolers were playful; with the parents it was the meetings and counseling; and with the professionals it was the training. The methodological qualification of the studies was considered low, which may be related to their limitations included in this review, mainly due to the types of designs adopted, the time and lack of continuity of interventions and sample size. Conclusion: food and nutrition education activities seem to be a promising strategy in knowledge, adoption of healthy eating practices and transmission of values in the school community.